Anticipated Employment Instability and Labor Market Equilibrium - O'Connor, James (Quarterly Journal of Economics, 1961)
Journal Article Anticipated Employment Instability and Labor Market Equilibrium Get access James O'Connor James O'Connor Barnard College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 1, February 1961, Pages 128–132, https://doi.org/10.2307/1883208 Published: 01 February 1961